An additional record of the non-indigenous species (NIS) Seriola fasciata from the southern coast of Sicily (Central Mediterranean Sea) - Geraci, Michele Luca (Array, 2020)
An additional record of the non-indigenous species (NIS) Seriola fasciata from the southern coast of Sicily (Central Mediterranean Sea) is here described in this note. The catch record is the first in the area and confirms the key role of the area for NIS spreading. In addition, an updated map of its spatial distribution is provided as well as a discussion on the possible misidentification and competition with the native greater amberjack Seriola dumerili.